Inclusion of emergency department patients in early stages of sepsis in a quality improvement programme has the potential to improve survival: a prospective dual-centre study. Issue 9 (17th May 2017) - De Groot, Bas; Struyk, Bastiaan; Najafi, Rashed; Halma, Nieke; Pelser, Loekie; Vorst, Denise; Mertens, Bart; Ansems, Annemieke; Rijpsma, Douwe
Abstract : Study objective: Sepsis quality improvement programmes typically focus on severe sepsis (ie, with acute organ failure). However, quality of ED care might be improved if these programmes included patients whose progression to severe sepsis could still be prevented (ie, infection without acute organ failure). We compared the impact on mortality of implementing a quality improvement programme among ED patients with a suspected infection with or without acute organ failure. Methods: This prospective observational study among ED patients hospitalised with suspected infection was conducted in two hospitals in the Netherlands. After stratification by sepsis category (with or without organ failure), in-hospital mortality was compared between a full compliance ( all quality performance measures achieved) and an incomplete compliance group. Multivariable logistic regression analysis was used to quantify the impact of full compliance on in-hospital mortality, adjusting for disease severity, disposition and hospital. Results: There were 1732 ED patients and 130 deaths. Full compliance was independently associated with approximately two-thirds reduction in the odds of hospital mortality ( adjusted OR of 0.30 (95% CI 0.19 to 0.47), which was similar in patients with and without organ failure. Among the 1379 patients with suspected infection without acute organ failure, there were 64 deaths, 15 (1.1%) in the full compliance group and 49 (3.6%) in the incomplete compliance group (mortality difference 2.5% (95% CI 1.6% to 3.3%)). Among 353 patients with organ failure, there were 66 deaths, 12 (3.4%) in the full compliance compared with 54 (15.3%) in the incomplete compliance group (mortality difference 11.9% (95% CI 8.5% to 15.3%)). Thus, there was a difference of 76 deaths between full and incomplete compliance groups, and 34 (45%) who benefited were those without acute organ failure. Conclusions: Sepsis quality improvement programmes should incorporate ED patients in earlier stages of sepsis given the potential to reduce in-hospital mortality among this population.